Existence of solutions for a biharmonic equation with gradient term - HAMYDY, Ahmed; MASSAR, Mohamed; ESSAOUINI, Hilal (Studia Universitatis Babeș-Bolyai Mathematica, 2023)
In this paper, we mainly study the existence of radial solutions for a class of biharmonic equation with a convection term, involving two real parameters. We mainly use a combination of the fixed point index theory and the Banach contraction theorem Mathematics Subject Classification (2010): 35K55, 35K65. Received 13 November 2020; Accepted 10 January 2021. Published Online: 2023-12-11 Published Print: 2023-12-30